EMPLOYEE TRAINING AND DEVELOPMENT: TRANSFORMATION TO A FUTURE-READY WORKFORCE AND THEIR PERFORMANCE OUTCOMES (Journal of Research Administration, 2023)
In the modern era, employee training and development are necessary for every organisation to expand and sustainably. Employees must go through a continuous process of development and enhancement if they are to assist in making them performers who are ready for the future. It is composed of a wide range of organised activities meant to improve and adjust employees' job-related skills, awareness, or perspective in order to achieve the organization's goals and objectives. Determining how worker efficiency and effectiveness are changed by training and development is one of the increasingly crucial tasks that directly influences an organization's success. With the hard and soft skills required to develop 21st-century workforces, organisations are committed to filling the gaps in their workforce. And their main tools are workplace growth and training. Since employees are a company's most valuable asset, their performance determines whether it succeeds or fails in the real world. Organisations would thrive and staff performance would rise with effective training and development plans. Therefore, the purpose of this research is to investigate the advantages that organisations provide for training and growth at various levels.Keywords: Skill development, behavioural changes, employee performance, Productivity.